VD_FINDINFO HC / 2014 / 270 vom 1. April 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, DROIT DE GARDE, OBLIGATION D'ENTRETIEN, MOTIVATION SOMMAIRE | 176 al. 3 CC, 311 al. 1 CPC (CH), 316 al. 3 CPC (CH)